Heads of departments' managerial skills and performance of local government departments: Evidence from seventeen selected local government authorities in Tanzania (Asian Journal of Economics and Business Management, 2022)
Local Government Authorities (LGAs) all over the world have experienced poor performance for many years. However, it has been confirmed that managerial skills are the bases for proper performance of Departments in the Local Government Authorities. What have been not clear are the influence of managerial skills on the performance of Local Government Departments in Tanzania. This study examined the influence of managerial skills on performance of selected Local Government Departments in Tanzania. The study used cross-sectional research design and purposive sampling techniques in selecting study areas and respondents. Data were collected through questionnaire (main instrument) from 290 Heads of Departments in selected Local Government Authorities in Tanzania. Descriptive statistics, factor analysis and Structural Equation Modelling was applied during data analysis. The study was guided by Management Competency Theory. The study found that managerial skills in terms of Administrative and technical skills had significant effect on the performance of selected Local Government departments in Tanzania. This study has also implications for practitioners (Heads of Departments). On the one hand, like previous research, study findings show that in order to achieve proper performance, LGAs should provide capacity building to their personnel (HoDs) in areas of financial management and technical skills.  In addition, managerial skills significantly influence revenue target and service delivery to the community. Thus, in order to improve performance of LGAs, the study concludes by recommending that for someone to be appointed as a Head of Department of LGAs in Tanzania, they must have managerial and technical skills related to financial matters for proper implementation of departmental operations and programmes and this should be part and parcel of the LGAs strategy and policy. The study also recommends that, the Local Authorities Accounts Committee (LAAC) to abide by the existing legal frameworks to control financial irregularities in the Departments of LGA and promote service delivery to the community. This will also reduce audit queries and control leakage of public funds in the LGAs.